Early growth according to protein content of infant formula: Results from the EDEN and ELFE birth cohorts. Issue 11 (11th May 2021) - Camier, Aurore; Davisse‐Paturet, Camille; Scherdel, Pauline; Lioret, Sandrine; Heude, Barbara; Charles, Marie‐Aline; de Lauzon‐Guillain, Blandine
Summary: Background: In several systematic reviews, rapid weight gain in early life has been related to increased risk of later obesity. In line with this finding, the "early protein hypothesis" suggests that reducing early protein intake is a potential lever for obesity prevention. Objective: To determine whether the variability of protein content of infant formula used in France over the period 2003‐2012 is significantly associated with early growth in children. Methods: A pooled sample of infants from the EDEN (Etude des Déterminants pré et postnatals de la santé et du développement de l'Enfant) mother‐child cohort (born in 2003‐2006) and the ELFE (Etude Longitudinale Française depuis l'Enfance) birth cohort (born in 2011) (ntotal  = 5846) was used. Protein content of the infant formula received at 4 months was classified into five groups. Associations between protein content (or breastfed status) at 4 months and weight‐, length‐ and BMI‐for‐age z‐scores at 6, 12 and 18 months were analysed by multivariable linear regression. Results: This analysis showed a positive association between protein content and weight‐, length‐ and BMI‐for‐age z‐scores at 6 months and only for weight‐for‐age at 12 months. At 6 months, as compared with the intermediate protein‐content group (2.1‐2.5 g/100 kcal), infants receiving very‐high protein content (>2.8 g/100 kcal) had higher BMI‐for‐age z‐score and those from the very‐low protein‐content group (<2.0 g/100 kcal) had lower BMI‐for‐age z‐score. Exclusively breastfed infants had lower length and weight z‐scores than formula‐fed infants at any age. Conclusions: Our findings show a positive association, under real conditions of use, between protein contents in infant formula still on the market and weight‐, length‐ and BMI‐for‐age z‐scores from 6 to 18 months.